3D application for learning programming concepts - Chen, Zhenni (2019)
With increase in the amount of computing courses offered by the universities, more students are taking computing in their tertiary education regardless of their experience in programming. However, with the fast pace learning curriculum introduced in universities, students often find themselves unable to catch up with the pace. In order to aid the students to catch up with the fast pace learning, the idea of an application to aid them in learning advanced programming concepts is developed to allow the users to learn advanced programming concepts using visual representations instead of the normal slide reading. In this report, the development and implementation of the application is explained.